A comparative study of archaeobotanical remains from Neolithic and Chalcolithic sites in Northern Fars, Iran - Ilkhani Moghadam, Hengameh (2020)
Fars is an area characterised by a great diversity not only in natural resources, but also in cultural and economic aspects. Reconstructing subsistence strategies of prehistoric settlements has always been one of the main objectives of the archaeological research undertaken in this region. In particular, discussions have been centred on whether the emphasis was on agricultural or pastoral activities. However, these arguments were mainly based on archaeological finds and settlement distributions rather than primary bioarchaeological evidence. The recent zooarchaeological studies in the region provided important insights into the prehistoric subsistence strategies practiced by the prehistoric inhabitants of Fars. However, the current archaeobotanical record of Fars is rather limited. Therefore, to shed more light, new macrobotanical remains (seeds and charcoal) were collected from three recently excavated sites in Fars namely Rahmatabad, Nurabad, and Mehrali. The analysed plant assemblages from these sites cover a long sequence of occupation from the late 8th to the Late 4th millennium B.C. The results of this study significantly expanded the archaeobotanical dataset of the region and added new important insights into the plant subsistence practices, woodland exploitation and fuel collection of these prehistoric communities. They indicated the likely importation of cereal crops (rather than a local domestication event), the significant role and exploitation practices of specific wild plant resources for food and fuel, and an overall regional variety and flexibility in subsistence practices. Ultimately, the comparison of these new data with other archaeobotanical evidence in Fars and the wider area significantly enhanced our understanding of prehistoric human-vegetation interactions.